Analysis of Mechanical Properties of Aluminum Alloy Metal Matrix Composite by Squeeze Casting – A Review. (2018) - Venkatesan, S.; Xavior, M. Anthony
Abstract: Most of the manufacturers are expecting to manufacture components in an economical way. Due to high defect rate in casting method manufacturers are facing huge loss. The main drawback of casting process is unavoidable defects such as blow holes, porosity and shrinkage etc., To overcome this issue, squeeze casting method can be adopted during the process. It is a challenging task to reduce or eliminate defects during casting process. This review article focus on the compilation of the work related to aluminium alloy metal matrix composite accomplished by various researchers main focus is on squeeze casting process and its process variably. The effectiveness and the influence of parameters on the mechanical characteristics are addressed in this paper. The influencing parameters such as temperature, processing method are considered during the investigation on mechanical characteristics of the composites.